Elaboración de una guía metodológica para la planeación y control de alcance, tiempo, costo y adquisiciones para la gerencia de proyectos de instalaciones eléctricas de media tensión y baja tensión de la empresa Cointelco S.A. (2017)
The Methodological Guide developed in this document, arises from the need evidenced in Cointelco S.A. To improve the chances of success of medium and low voltage electrical infrastructure projects. In order to respond to this need, a Methodological Guide is structured for the planning and control processes of the scope, time, cost and acquisition areas of such projects of the organization.